2021
DOI: 10.3390/bs11070098
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Family Conflicts and Fear of Injecting: Perception Differences between Preadolescents and Adolescents with Type 1 Diabetes and Their Mothers

Abstract: Good management of diabetes requires at the same time self-regulation behaviour and a balanced involvement of family components. This cross-sectional study’s aims were: understanding fear of injections and perceptions of family conflicts in preadolescents and adolescents with type 1 diabetes mellitus and their mothers, comparing their perceptions, and identifying the risk factors impacting patients’ quality of life. Eligibility criteria were: treatment for diabetes mellitus type I, currently aged 10–18 years, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Studies showed that over half of patients were reluctant to receive insulin therapy due to needle pain, and the fear of self-injecting is common in adolescents with Type I diabetes. 4,5 Thus, finding a pain-free or non-invasive way to administer therapeutic macromolecules such as insulin is important to improve the patient compliance and ultimately, their quality of life. Many non-invasive administration routes have been studied preclinically and clinically, including oral or nasal administration or delivery via topical and transdermal routes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that over half of patients were reluctant to receive insulin therapy due to needle pain, and the fear of self-injecting is common in adolescents with Type I diabetes. 4,5 Thus, finding a pain-free or non-invasive way to administer therapeutic macromolecules such as insulin is important to improve the patient compliance and ultimately, their quality of life. Many non-invasive administration routes have been studied preclinically and clinically, including oral or nasal administration or delivery via topical and transdermal routes.…”
Section: Introductionmentioning
confidence: 99%
“…During adolescence, the increased need for insulin, greater desire for independence, immature cognitive function, and more time spent out of the house can disrupt these routines and potentially lead to unwanted complications ( 7 , 8 ). Moreover, adolescents’ changing relationship with their parents during this period, which is often marked by increased conflict, and the transfer of responsibility for T1DM management from parents to adolescents make it more difficult for parents to be involved in the process and reduces treatment adherence ( 9 , 10 , 11 ). Adolescents with T1DM are also susceptible to mental health disorders, such as diabetes distress and depression ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each response is graded on a 4-point Likert scale; 1: almost never, 2: Sometimes, 3: Often, 4: Almost all the time. Calculating the mean raw score for each sub-dimension was conducted and higher scores indicate greater fear, and the D-FISQ total score extends from 0 to 45 [15][16][17]. A score of ≥6 is considered a positive fear of injection.…”
Section: Minimal Sample Size Calculationmentioning
confidence: 99%